Prevalence of tobacco and areca-nut use among patients attending dental teaching hospital in the central province of Sri Lanka and its association with oral mucosal lesions; a cross sectional study - Sumali Sumithrarachchi; Isuru Athukorala; Fazly Rumy; Ruwan Jayasinghe (Elsevier, 2024)
Introduction: Tobacco and areca-nut are risk factors for oral cancer and potentially malignant disorders. Oral cancer is ranked as the commonest among males in Sri Lanka (18.4 %). This research aims to determine the prevalence of tobacco and areca-nut use and its association with oral lesions. Method: It is a cross-sectional study using 368 patients attending the Dental Diagnostic Clinic. Details of tobacco and areca-nut use were collected and participants were examined for mucosal lesions. Results: It revealed that 23.9 % had tobacco use. Out of these, 41.1 %, 22.2 % and 36.7 % had smokeless-tobacco use, smoking and both, respectively. Similarly, 25.3 % had areca-nut/betel-quid use and majority (72.8 %) added tobacco to it. Tobacco (93.2 %) and areca-nut (79.6 %) use was higher among males (p < 0.05). Significant associations of areca-nut use with age (p = 0.001) and education level (p = 0.025) were noted. Oral lesions like de-pigmentation, white patches, ulcers, growths and oral sub-mucous fibrosis (OSF) had prevalences of 2.4 % each. Prevalence of pigmentation, lobulated tongue and erosive lesions was 10.6 %, 4.6 % and 1.4 %, respectively. 32.6 % had abnormalities like linea-alba, periodontal problems, pericoronitis and hairy tongue. The study revealed that >90 % of those who used tobacco and areca-nut had oral lesions (p < 0.05). Conclusion: The prevalence of tobacco and areca-nut use is high among patients attending the Dental Teaching Hospital, and its association with mucosal lesions is significant. Hence regular awareness programs on the adverse effects of tobacco and areca-nut use should be carried out at the Diagnostic clinic as a preventive measure.